Combining Kalman Filtering with ZigBee Protocol to Improve Localization in Wireless Sensor Network. (21st March 2013) - El Madani, Bouchra; Yao, Anne Paule; Lyhyaoui, Abdelouahid
Abstract : We propose a low-cost and low-power-consumption localization scheme for ZigBee-based wireless sensor networks (WSNs). Our design is based on the link quality indicator (LQI)—a standard feature of the ZigBee protocol—for ranging and the ratiometric vector iteration (RVI)—a light-weight distributed algorithm—modified to work with LQI measurements. To improve performance and quality of this system, we propose three main ideas: a cooperative approach, a coefficient delta (δ ) to regulate the speed of convergence of the algorithm, and finally the filtering process with the extended Kalman filter. The results of experiment simulations show acceptable localization performance and illustrate the accuracy of this method.